Identification of antibacterial activity of LEAP2 from Antarctic icefish Chionodraco hamatus - Yueyue Fei; Qin Wang; Jigang Lu; Linyue Ouyang; Wei Li; Ruiqin Hu; Liangbiao Chen (Journal of Fish Diseases, 2023)
Liver‐expressed antimicrobial peptide 2 (LEAP2) is a small peptide, which is consisted of signal peptide, pro‐peptide and the bioactive mature peptide. Mature LEAP2 is an antibacterial peptide with four highly conserved cysteines forming two intramolecular disulfide bonds. Chionodraco hamatus , an Antarctic notothenioid fish that lives in the coldest water, has white blood unlike most fish of the world. In this study, the LEAP2 coding sequence was cloned from C. hamatus , including a 29 amino acids signal peptide and mature peptide of 46 amino acids. High levels of LEAP2 mRNA were detected in the skin and liver. Mature peptide was obtained by chemical synthesis in vitro, displayed selective antimicrobial activities against Escherichia coli , Aeromonas hydrophila , Staphylococcus aureus and Streptococcus agalactiae . Liver‐expressed antimicrobial peptide 2 showed bactericidal activity by destroying the cell membrane integrity and robustly combined with bacterial genomic DNA. In addition, overexpression of the Tol‐LEAP2‐EGFP in zebrafish larva showed stronger antimicrobial activity in C. hamatus than in zebrafish, accompanied by lower bacterial load and expression of pro‐inflammatory factors. This is the first demonstration of the antimicrobial activity of LEAP2 from C. hamatus , which is of useful value in improving resistance to pathogens.